Vitamin D levels condition the outcome benefits of renin-angiotensin system inhibitors (RASI) among patients undergoing percutaneous coronary intervention. (October 2020) - Verdoia, Monica; Nardin, Matteo; Rolla, Roberta; Negro, Federica; Gioscia, Rocco; Saghir Afifeh, Arraa Maddalena; Viglione, Filippo; Suryapranata, Harry; Marcolongo, Marco; De Luca, Giuseppe; ,
Graphical abstract: Abstract: Background: Vitamin D deficiency is estimated as the most common medical condition worldwide, with severe implications on survival and on several inflammatory, immune-mediated and thrombotic disorders, and especially for cardiovascular disease. Recent studies have suggested that vitamin D could directly regulate the Renin-Angiotensin System (RAS) activity, therefore potentially interfering with the pharmacological effects of RAS Inhibitors (RASI), an issue that has seldom been explored. Therefore, the aim of the present study was to evaluate the prognostic impact of the use of RASI according to vitamin D levels among patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). Methods: Consecutive patients undergoing PCI were included. Main clinical features and chemistry parameters were assessed at admission. Vitamin D levels were measured by chemiluminescence immunoassay kit LIAISON® Vitamin D assay (Diasorin Inc). Severe deficiency was defined for 25(OH)D < 10 ng/mL. The primary study endpoint was defined as the occurrence of major cardiovascular events (MACE, a composite of death, recurrent Myocardial Infarction (MI) and target vessel revascularization) at the longest available follow-up. Results: We included a total of 705 patients, that were divided according to vitamin D tertiles (< 12.7 ng/mL; 12.7–21.59 ng/mL; ≥21.6 ng/mL) and use of RASI. RASI therapy was significantly associated to arterial hypertension, creatinine, lower 25(OH)D, use of statins, diuretics, ASA and ticagrelor across vitamin D tertiles. At a median follow-up of 996 [377–1552] days, MACE occurred in 174 (24.7 %) patients. Severe hypovitaminosis D was significantly associated with a higher rate of MACE (HR[95 %CI] = 0.75[0.62−0.91], p = 0.004). The use of RASI significantly lowered the rate of MACE in patients with lower vitamin D (I tertile: 41.3 % vs 25.9 %, adjusted HR[95 %CI] = 0.43[0.26−0.73], p = 0.002); whilst a non-significant effect was observed for II and III tertiles values (18.6 %vs 29.5 %, adjusted HR[95 %CI] = 1.16[0.57−2.34], p = 0.69, and 21.2 % vs 12.6 %, adjusted HR[95 %CI] = 1.1[0.46−2.62], p = 0.83) (p int = 0.04). A similar prognostic interaction for RASI and vitamin D was observed for cardiovascular mortality and MI (p int = 0.03). Conclusion: Among patients undergoing PCI, the use of RASI was associated with lower risk of MACE only among patients with lower levels of vitamin D. Future larger studies are certainly warranted in order to define the prognostic implications of vitamin D supplementation on the RAS system modulation, especially among patients treated with RASI.